Ultrasound-Guided Occipital Nerve Blocks as Part of Multi-Modal Perioperative Analgesia in Pediatric Posterior Craniotomies: A Case Series - Jordan I. Gaelen; Michael R. King; John Hajduk; Angelica Vargas; David J. Krodel; Ravi D. Shah; Hubert A. Benzon (MDPI AG, 2023)
Various regional anesthetics have been used for postoperative analgesia for pediatric craniotomy. In this case series, we report retrospectively collected data on postoperative pain and analgesic use in 44 patients who received ultrasound-guided occipital nerve blocks in addition to intravenous analgesic agents for posterior craniotomy procedures. In the immediate post-anesthesia care unit, pain was rated as zero or well controlled in 77% of patients, with only 43% requiring intravenous or demand patient-controlled analgesia opioids. There were no block-related complications. Occipital nerve blocks may constitute a safe and effective component of multimodal analgesia in this population.